Evaluation of an alternative sorbent for passive sampling of the herbicides 2, 4-D and Dicamba in the air. Issue 7 (3rd August 2021) - Ceolin, Bruna Christofari; Kemmerich, Magali; Noguera, Matheus Machado; Camargo, Edinalvo Rabaioli; Avila, Luis Antonio de
Abstract: The present study aimed to evaluate the Strata-X ® sorbent, commonly used in cartridges, through analysis by high-performance liquid chromatography coupled with mass spectrometry. Due to the different physical-chemical characteristics of the compounds, different conditions of chromatography and mass analysis were necessary. The developed methods were validated in terms of selectivity, linear range, linearity (coefficient of determination, r 2 ), the limit of detection (LOD), the limit of quantification (LOQ), accuracy (recovery, %), and precision (RSD, %). The results allowed us to select efficient extraction methods, using methanol acidified to pH 2 with formic acid, to elute the herbicides 2, 4-D and dicamba in both sorbent materials. Besides, the Strata-X ® sorbent was efficient in the sorption of analytes; thus, we indicate it for potential use in air sampling as an alternative to XAD-2.